Since JL is a perpendicular bisector of segment KM, it means that point H (on JL) is the midpoint of segment KM. Therefore, the lengths KH and HM are equal.
We can set up the equation based on the given lengths:
\[ KH = HM \]
Substituting the expressions provided:
\[ 6y + 3 = 2y + 7 \]
To solve for \(y\), we first isolate the \(y\) terms. Begin by subtracting \(2y\) from both sides:
\[ 6y - 2y + 3 = 7 \]
This simplifies to:
\[ 4y + 3 = 7 \]
Next, subtract 3 from both sides:
\[ 4y = 4 \]
Now, divide by 4:
\[ y = 1 \]
Now, we need to find the length of segment \(HM\). We can use the expression for \(HM\) and substitute \(y = 1\):
\[ HM = 2y + 7 \]
Substituting \(y\):
\[ HM = 2(1) + 7 = 2 + 7 = 9 \]
Thus, the length of segment \(HM\) is:
\[ \boxed{9} \] units.